Analisis Pengendalian Intern Pada Efektifitas Pengelolahan Kas PT. Abadi Sakti Mitra Mandiri Lampung - Wati, Dirma; Riswan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to describe the cash management phenomenon occurring at PT. Abadi Sakti Mitra Mandiri Lampung. The author has conducted research on cash management with an emphasis on efficiency and effectiveness through internal monitoring and control methods. Therefore, financial monitoring and control must be a top priority for management. The subject of this study is PT. Abadi Sakti Mitra Mandiri Lampung. The research method used is the Grounded Research method, which is based on facts, applying comparative analysis for empirical generalization, conceptualization, theory verification, and theory development, with data collection and analysis carried out simultaneously. The results of this research indicate that there are problems in internal control activities, especially related to holding multiple positions. Therefore, companies are advised to open job vacancies so as not to experience a shortage of human resources which could lead to multiple positions.